1986
DOI: 10.5014/ajot.40.8.546
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Articulation Disorders and Motor Coordination in Children

Abstract: This study was designed to examine the relationship between articulation disorders, soft neurological signs, and motor abilities. Fifteen children with articulation problems, as measured by the Templin-Darley Articulation Screening Test and a connected speech sample, were compared with a normal control group (matched for sex and age) on the Quick Neurological Screening Test, the Imitation of Postures test (from the Southern California Sensory Integration Tests), and the 1984 version of the Stott Test of Motor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
3

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 12 publications
2
21
0
3
Order By: Relevance
“…In this case, Archer and Witelson (1988) found that children with developmental dysphasia were signi cantly slower than their normally developing peers in the accurate production of such postures. Other studies found no diVerences in time and accuracy of non-symbolic single gesture production (Cermak et al 1986, Hill 1998, Smith and Bryson 1998. Finally, four studies assessed the production of non-symbolic hand sequences (two and/or three postures per sequence).…”
Section: Praxis Abilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, Archer and Witelson (1988) found that children with developmental dysphasia were signi cantly slower than their normally developing peers in the accurate production of such postures. Other studies found no diVerences in time and accuracy of non-symbolic single gesture production (Cermak et al 1986, Hill 1998, Smith and Bryson 1998. Finally, four studies assessed the production of non-symbolic hand sequences (two and/or three postures per sequence).…”
Section: Praxis Abilitymentioning
confidence: 99%
“…Five of the studies reported in table 1 included the Movement ABC, or its predecessor the TOMI, as one of the motor tests used with a sample of children with SLI. A signi cant number of the children in each of these studies fell at or below the 15th percentile on the Movement ABC: with 40, 60, 71 and 90% for Cermak et al (1986), Hill (1998), , Rintala et al (1997) and Robinson (1991) respectively. This is in contrast to the estimated prevalence of DCD being~6% (APA 1994).…”
Section: Nature Of the Motor De Citsmentioning
confidence: 99%
“…The goal of evaluating the peripheral speech mech anism is to obtain information about the speaker's motor control and control of the major articulators. Some studies [2,4,27] have shown that children with articulatory disorders have difficulties performing voli tional oral movements and sequencing these movements. In fact, faulty articulation -even mildly faulty articulation [28][29][30] -may be a sign of developmental dyspraxia of speech [21.…”
Section: Discussionmentioning
confidence: 99%
“…The speech motor performance of normal ly developing children is known to improve with age and, on the other hand, children with misarticulations have been reported to have poorer oral motor skills [1] and difficulty in the motor control of speech [2][3][4], Conclusions concerning the anatomical and neuromuscular maturation of the speech mechanism have been drawn mainly from acoustic studies [5][6][7], which provide indirect information on the activities of the articula tors. As the technique for gaining kinetic in formation should be noninvasive and present no physical or psychological risk to the child, only a limited number of instrumental tech niques are suitable for use with children [8].…”
Section: Introductionmentioning
confidence: 99%
“…Because the information processing test that we used in our study, was also reflecting some components of central auditory processing. Cermak et al [30] performed both motor impairment test and quick neurological screening test to children with articulation disorder.…”
mentioning
confidence: 99%